A clean process for alumina extraction and ferrosilicon alloy preparation from coal fly ash via vacuum thermal reduction. (10th December 2019) - Xue, Yang; Yu, Wenzhou; Mei, Jie; Jiang, Weiyan; Lv, Xuewei
Abstract: Owing to high content of alumina in coal fly ash (CFA), recovering alumina from CFA has gained great interest from governments and scientists in recent years. With the aim of further reducing the cost as well as protecting the environment, a clean process to recover alumina and simultaneously produce ferrosilicon alloy from CFA by a vacuum technology was suggested in this paper. The overall process was composed of vacuum thermal reduction, sieving and magnetic separation. Thermodynamic calculations indicated that the initial decomposition temperature of stable mullite in CFA can decrease from 1367 to 1023 K as the CO partial pressure drops from 1 to 0.001 atm. The experimental results also proved that a vacuum environment can promote the mullite to decompose at a lower temperature. Simultaneously, the formation temperature of ferrosilicon alloys decreased greatly with using the vacuum thermal reduction. The produced ferrosilicon alloys and the residual alumina in reduced samples could be separated effectively in subsequent sieving and magnetic separation processes, and the separation efficiency depended not only on the reduction temperature, but also on the reduction duration. As the reaction temperature was 1473 K and the reduction duration was 6 h, the recovery rate of alumina reached 82.61%, and the content of alumina in the non-magnetic portion was 87.02%. Compared with the traditional route of alumina extraction, e.g., lime stone sinter process, there was almost no waste slag produced by vacuum thermal reduction process. Therefore, this provides a new idea for the environmentally friendly utilization of CFA. Graphical abstract: Image 10670 Highlights: A clean alumina extraction from coal fly ash via vacuum method was proposed. The decomposition temperature of mullite decreased greatly in the vacuum condition. Sieving and magnetic separation can separate Fe–Si alloy and alumina effectively. The recovery rate of alumina can reach 82.61% in the laboratory.